Methylene blue decolorizing bacteria isolated from water sewage in Yogyakarta, Indonesia - Michelle; Rachel Arvy Nabasa Siregar; Astia Sanjaya; Jap Lucy; Reinhard Pinontoan (Society for Indonesian Biodiversity, 2020)
Abstract. Michelle, Siregar RAN, Sanjaya A, Jap L, Pinontoan R. 2020. Methylene blue decolorizing bacteria isolated from water sewage in Yogyakarta, Indonesia. Biodiversitas 21: 1136-1141. The textile industry contributes to water pollution issues all over the world. One of the most commonly applied cationic dye in the textile industry is methylene blue. This study aimed to isolate bacteria with the potential to decolorize methylene blue from dye contaminated sewage water located in Kulon Progo District, Yogyakarta, where several textile industries within the proximity, are located. Characterizations of bacterial candidates were done morphologically and biochemically. Molecular identification was conducted by 16S rRNA sequencing. The ability of isolates to decolorize methylene blue was observed by the reduction of methylene blue’s maximum absorption at the wavelength of 665 nm. The results showed that isolates were identified as Comamonas aquatica and Ralstonia mannitolilytica. C. aquatica PMB-1 and R. mannitolilytica PMB-2 isolates were able to decolorize methylene blue with decolorization percentage of 67.9% and 60.3%, respectively when incubated for 96 hours at 37°C. These findings present information on the capability of the genus Ralstonia and Comamonas to decolorize methylene blue cationic dye.